Indonesia’s Carbon Tax: To What Extent is it Effective in Achieving the Goals? - Siregar, Syahrituah; Fatah, Luthfi; Imansyah, M. Handry; Sunardi, Sunardi (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — This study offers another perspective on carbon taxation in Indonesia by presenting sector-specific estimates of potential revenue and emission reductions using a more grounded input-output framework. Unlike many studies that rely on macro-level assumptions, this research integrates detailed CO₂ emission data by sector and applies a forecasting approach to generate practical insights for policy implementation. Research Objective — The main objectives are to estimate the carbon tax revenue that could be collected and to assess how much emission reduction could be achieved through this policy, particularly in relation to Indonesia’s enhanced Nationally Determined Contribution (NDC) targets. Research Methods — Using the 2016 input-output table enriched with a CO₂ satellite account, and applying the double exponential smoothing method to forecast future emissions, the study simulates the impact of a carbon tax set at IDR 30,000 per ton. Empirical Results — The results indicate that annual revenue from the carbon tax could reach between IDR 25.195 trillion and IDR 25.21 trillion during the 2025–2030 period, totalling approximately IDR 151.19 trillion. By 2030, national emissions are projected to fall to 839.93 million tons of CO₂, which is 49.68% lower than the business-as-usual (BAU) level, 35.94% below the counter measure 1 (CM1) level, 31.33% below counter measure 2 (CM2), and 17.28% lower than projections without tax implementation. Implications — These findings highlight the important—though not solitary—role of carbon taxation in closing the emission gap and supporting Indonesia’s transition toward a low-carbon and climate-resilient economy. The approach used in this study may serve as a useful reference for other countries considering similar measures.